FEATURES OF THE PSYCHOLOGICAL STATE OF HIV-INFECTED PERSONS ACCORDING TO ANXIETY LEVEL - Serheta , Ihor; Dudarenko , Oksana (Collection of scientific papers «ΛΌГOΣ», 2023)
From the first day of the diagnosis of “HIV infection” significant emotional experiences arise and pronounced deviations in the state of neuropsychological and somatic health of HIV-infected persons are registered. Moreover, the emotional experiences of an HIV-infected person are, in most cases, associated with the occurrence of suffering and require medical, social and psychohygienic correction [2, 3]. With any serious or incurable disease, there is a need to restructure the orientation of the individual. According to some authors, serious mental disorders appear in HIV-positive people. The pathological process creates conditions for the functioning of psychological mechanisms that have no place in “normal" mental development and can lead to distorted personality development [1, 2, 4, 5].